Ocean Wave Rendering with Whitecap in the Visual System of a Maritime Simulator - Chen, Lining; Jin, Yicheng; Yin, Yong (Journal of computing and information technology, 2017)
The whitecap is an important oceanographic phenomenon. However, existing whitecap rendering methods do not successfully generate realistic whitecaps. To solve this problem, this paper presents a real-time whitecap rendering method applied to the visual system of a maritime simulator. The method takes the vertical acceleration on the wave crest as the criterion of whitecap generation. The Fourier coefficient of the vertical acceleration is provided, and a continuous mathematical model computing the whitecap coverage is built. The vertical acceleration is the variable of the model. The lifetime of the whitecap's existence can be controlled by the parameter of the model, and the parameter is computed with the genetic algorithm. The average of the computed whitecap coverage is equal to the whitecap coverage computed by the stochastic method and is close to the whitecap coverage computed by the empirical formula. The whitecap coverage is used as the blending factor to blend the pixel color of the whitecap texture and that of the sea surface. The presented method has sound theoretical support, with small computational complexity. The rendered whitecap is closer to the description of the Beaufort wind force scale than before.